Drivers of medium- and large-bodied terrestrial mammal communities within a savannah–forest mosaic on Makushi and Wapichan customary lands in the Rupununi, Guyana - Matthew T. Hallett; Francesco Rovero; Nathalie Van Vliet; Fernando M. Li; Rhomayne Li; Jeremy Melville; Asaph Wilson; Howard Barnabas; Andrew Albert; Dexter Da Silva; Erin Earl; Oswin David; et al. (Oryx)
The savannah–forest mosaic of the Rupununi region of Guyana is a dispersal corridor between large tracts of intact Guiana Shield forests and a subsistence hunting ground for Indigenous Makushi and Wapichan communities. We conducted a camera-trap survey at 199 sites across four major forested habitat types and used multi-species occupancy modelling to determine regional-scale drivers of mammalian occupancy at both species and community levels, accounting for imperfect detection. We detected 47 savannah- and forest-dwelling mammal species, with the occupancy of medium- and large-bodied terrestrial mammal species (community occupancy) positively related to per cent forest cover and negatively to the presence of gallery forest habitat. The occupancy of 15 of 30 species was positively related to forest cover, suggesting the importance of maintaining forested habitat within the broader mosaic comprising savannahs and intermediate habitats for sustaining maximum mammal diversity. Jaguar Panthera onca occupancy was associated with the presence of livestock, and giant anteater Myrmecophaga tridactyla occupancy was negatively associated with distance to the nearest road, both results of concern in relation to potential human–wildlife conflict. The probability of detecting terrestrial mammal species (community detectability) increased away from villages, as did the detectability of two large-bodied, hunted species, the lowland tapir Tapirus terrestris and collared peccary Pecari tajacu, potentially indicating the negative effects of subsistence and commercial hunting in this savannah mosaic habitat. We use our findings to discuss how management strategies for hunting, fire, timber harvest and agriculture within Indigenous titled lands could help ensure the sustainability of these traditional livelihood activities.